Biurokratyczne załatwianie spraw - Świderski, Krzysztof (Studia Prawa Publicznego, 2021)
The article presents the issue of a bureaucratic disposal of matters by public administration authorities. The letter of dissatisfaction was introduced into Polish law as early as 1950. It was an expression of a negative attitude towards red tape. The prohibition of a bureaucratic disposal of matters is a guideline for the entire public sector. Bureaucracy is the negative behavior of officials: learned helplessness, routine, prejudices against applicants, assurance, conformism, and excessive formalism. The legislator’s pejorative assessment does not refer to bureaucracy itself, but to red tape as a dysfunction of bureaucracy. Red tape is the result of organizational culture. The article presents the model of Weberian bureaucracy and a critique of it. The provisions obliging officials to act in an fair, impartial, reasonable and proper manner are discussed, and the example is given of proper, open, efficient and independent European Union administration. The tool that determines bureaucracy is the document. The creation of excessive amounts of documents, as a manifestation of bureaucracy (red tape), is closely related to the development of office techniques. However, the development of information technology and the dissemination of electronic communication channels have changed the face of bureaucracy. The direct contact between an official with an applicant is changing into screen-level bureaucracy, with the claimant’s application being handled by the IT system. The official’s discretionary power has Hus been significantly reduced. The development of e-administration eliminates inappropriate actions of officials. However, a new type of bureaucracy is emerging by IT experts. Art. 227 of the Code of Administrative Proceedings can become a protective measure against the formalism of e-government.